1996
DOI: 10.1007/bf00014882
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate and carbon metabolite accumulation responses in leaves of ozone tolerant and ozone susceptible spinach plants after acute ozone exposure

Abstract: The objective of this study was to determine whether exposure of plants to ozone (O3) increased the foliar levels of glucose, glucose sources, e.g., sucrose and starch, and glucose-6-phosphate (G6P), because in leaf cells, glucose is the precursor of the antioxidant, L-ascorbate, and glucose-6-phosphate is a source of NADPH needed to support antioxidant capacity. A further objective was to establish whether the response of increased levels of glucose, sucrose, starch and G6P in leaves could be correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…When plants are exposed to ozone, an accumulation of carbohydrates including starch occurs (Robinson & Rowland, 1996;Einig et al, 1997;Trumble et al, 1987;Grantz & Farrar, 1999;Lux et al, 1997). We have found a similar response in B. rapa since ozone fumigation caused a significant increase in the starch level in the sensitive line and the resistant line.…”
Section: Carbohydrates and Other Biochemical Measuressupporting
confidence: 76%
See 2 more Smart Citations
“…When plants are exposed to ozone, an accumulation of carbohydrates including starch occurs (Robinson & Rowland, 1996;Einig et al, 1997;Trumble et al, 1987;Grantz & Farrar, 1999;Lux et al, 1997). We have found a similar response in B. rapa since ozone fumigation caused a significant increase in the starch level in the sensitive line and the resistant line.…”
Section: Carbohydrates and Other Biochemical Measuressupporting
confidence: 76%
“…Ozone is a gaseous pollutant and acts as a phytotoxin through reactions in the leaves with the subsequent production of highly oxidative intermediates (Robinson & Rowland, 1996). This induction of stress on the plants, along with other types of plant stresses such as drought, nutrient deficiency, and herbivory is the cause of a series of short and long-term biochemical and growth-related alterations (Herold, 1980).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of the experiments in the present study revealed a decrease in photosynthesis rates ranging from 13% to 27% (interspecific) and 20-31% (intraspecific). Similar results have been found for spinach cultivars which were exposed to 250 ppb O 3 for a 6.5 h acute exposure, with photosynthetic rates of cv Winter reduced by 48.9% and cv Nordic by 66.2% (Robinson and Rowland 1996). Calatayud et al (2002a) also found that the photosynthetic rate of lettuce leaves was reduced by 77% (compared to filtered air) after O 3 exposure (66 ppb, 12 h day −1 for 90 days).…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, an increase in background O 3 levels in regions of the northern hemisphere may occur in the near future (The Royal Society 2008). O 3 is a gaseous pollutant which causes toxicity to plants at macro-and microscopic levels, when its concentrations exceed species-specific thresholds, through reactions in the leaves, with a subsequent production of highly oxidative intermediates (Robinson and Rowland 1996;Oksanen et al 2013;Vaultier and Jolivet 2015). Such exceedances may result in reduction in plant vigor, suppression of yields and productivity, with further implications to ecological processes and trophic cascades (Feng et al 2008;Lindroth 2010;Ainsworth et al 2012;Koike et al 2013;Blande et al 2014; 2016a; Chappelka and Grulke 2016).…”
Section: Introductionmentioning
confidence: 99%